Candidate Gene Polymorphisms Influence the Susceptibility to Salt Sensitivity of Blood Pressure in a Han Chinese Population: Risk Factors as Mediators - Xie, Yunyi; Liu, Zheng; Liu, Kuo; Qi, Han; Peng, Wenjuan; Cao, Han; Liu, Xiaohui; Li, Bingxiao; Wen, Fuyuan; Zhang, Fengxu; Zhang, Ling (Frontiers in Genetics, 2021)
Genome-wide association studies suggest that there is a significant genetic susceptibility to salt sensitivity of blood pressure (SSBP), but it still needs to be verified in varied and large sample populations. We attempted to verify the associations between single-nucleotide polymorphisms (SNPs) in candidate genes and SSBP and to estimate their interaction with potential risk factors. Twenty-nine candidate SNPs were genotyped in the 2057 northern Han Chinese population from the Systems Epidemiology Study on Salt Sensitivity. A modified Sullivan's acute oral saline load and diuresis shrinkage test (MSAOSL-DST) was used to identify SSBP. A generalized linear model was conducted to analyze the association between SNPs and SSBP, and Bonferroni correction was used for multiple testing. Mediation analysis was utilized to explore the mediation effect of risk factors. Eleven SNPs in eight genes (PRKG1, CYBA, BCAT1, SLC8A1, AGTR1, SELE, CYP4A11, and VSNL1) were identified to be significantly associated with one or more SSBP phenotypes (P<0.05). Four SNPs (PRKG1/ rs1904694 and rs7897633, CYP4A11/ rs1126742, and CYBA/rs4673) were still significantly associated after Bonferroni correction (P<0.0007) adjusted for age, sex, fasting blood glucose, total cholesterol, diet, physical activity, and hypertension. Stratified analysis showed that CYBA/rs4673was significantly associated with SSBP in hypertensive subjects (P<0.0015) and CYP4A11/ rs1126742 was significantly associated with SSBP in normotensive subjects (P<0.0015). Subjects carrying both CYBA/rs4673-AA and AGTR1/rs2638360-GG alleles have a higher genetic predisposition to salt sensitivity due to the potential gene coexpression interaction. Expression quantitative trait loci analysis (eQTL) suggested the above positive four SNPs showed cis-eQTL effects on gene expression levels. Mediation analysis suggested that several risk factors were mediators of the relation between SNP and SSBP. This study suggests that genetic variants in eight genes might contribute to the susceptibility to SSBP, and other risk factors may be mediators.